Molecular Editing of Indoles via Formal N-Atom Insertion and C–S Cross-Coupling in Micellar Solution - Valentine, Gemma (2023)
The research reported in this thesis consists of two distinct projects. The latter of which will be introduced in a subsequent abstract following discussion of the preliminary project.